Are some owners better than others in Czech privatized firms? even meta-analysis can't make us perfectly sure - Iwasaki, Ichirō 1966-; Kočenda, Evžen 1963- (Leibniz Institute for Eastern and Southeastern European Studies, 2017)
We use a total of 1171 estimates extracted from 34 previous studies and perform a meta-analysis to examine the relationship between ownership structures and firm performance in the Czech mass-privatized firms. We find that, in contrast to the remarkable effect of foreign ownership on firm performance and restructuring activities, domestic private entities were incapable of outperforming the state as owners of Czech companies. Our assessment of publication selection bias, however, indicates that the collected estimates do not contain genuine evidence for many types of corporate ownership. Further development and improvement in this study area are necessary to capture the true effect. Finally, we also point at the importance to draw (metaanalysis) inferences based on studies that employ adequate methodology.
Keywords: Geschichte 1989-2009; Privatisierung; Metaanalyse; Unternehmen; Staatsunternehmen; Tschechien